Age and origin of middle Neoproterozoic mafic magmatism in southern Yangtze Block and relevance to the break-up of Rodinia - Zhou, J.; Li, X.; Ge, W.; Li, Zheng-Xiang (International Association for Gondwana Research, 2007)
SHRIMP U–Pb zircon age, geochemical and Sm–Nd isotopic data are reported for mid-Neoproterozoic volcanic rocks and mafic intrusions in northern Guangxi (Guibei) and western Hunan (Xiangxi) Provinces along the southern margin of the Yangtze Block. The mafic igneous rocks studied are generally synchronous, dated at ~765 Ma. The least-contaminated dolerite samples from Xiangxi are characterized by high eNd(T) value of 3.3 to 5.3 and OIB-type geochemical features, indicating that they were derived from an OIB-like mantle source in a continental rift setting. The spilites and gabbros in Guibei show basaltic compositions transitional between the tholeiitic and calc-alkaline series. Despite depletion in Nb and Ta relative to La and Th, they have Zr/Sm=27–35 and Ti/V=30–40, affinitive to intraplate basalts. Their eNd(T) values are variable, ranging from -1.2 to 3.2 for the spilites and from -1.7 to 2.9 for the gabbros, suggesting that these spilites and gabbros crystallized from crustalcontaminated mafic magmas derived from a metasomatised subcontinental lithospheric mantle source. We conclude that the ~765 Ma mafic magmatic rocks in Guibei and Xiangxi were formed in a single continental rift setting as part of the broadly concurrent ~780–750 Ma rift magmatism over much of South China, which may be related to the plume activities during the breakup of Rodinia.